2022
DOI: 10.3389/fonc.2022.846232
|View full text |Cite
|
Sign up to set email alerts
|

The Discrepancy Between Standard Histologic WHO Grading of Meningioma and Molecular Profile: A Single Institution Series

Abstract: IntroductionMeningiomas are the most common primary central nervous system (CNS) tumor. They are most often benign, but a subset of these can behave aggressively. Current World Health Organization (WHO) guidelines classify meningiomas into three grades based on the histologic findings and presence or absence of brain invasion. These grades are intended to guide treatment, but meningiomas can behave inconsistently with regard to their assigned histopathological grade, influencing patient expectations and manage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“… Roehrkasse et al (2022) have reported data supporting the concept that the analysis of the molecular background of meningiomas may hold superior prognostic power when compared to histological features. Nassiri et al (2021) described four consensus molecular meningioma groups with distinct tumour behaviour.…”
Section: Pathophysiology and Molecular Profile Of Cns Invasionmentioning
confidence: 88%
See 1 more Smart Citation
“… Roehrkasse et al (2022) have reported data supporting the concept that the analysis of the molecular background of meningiomas may hold superior prognostic power when compared to histological features. Nassiri et al (2021) described four consensus molecular meningioma groups with distinct tumour behaviour.…”
Section: Pathophysiology and Molecular Profile Of Cns Invasionmentioning
confidence: 88%
“… Nassiri et al (2021) described four consensus molecular meningioma groups with distinct tumour behaviour. Comprehensive molecular profiling of meningiomas should probably include DNA methylation pattern and copy number aberration analyses, investigating mRNA abundance, as well as driver mutations of oncogenes, such as BAP1, CDKN2A/B , and the TERT promoter ( Louis et al, 2021 ; Nassiri et al, 2021 ; Roehrkasse et al, 2022 ). Maas et al reviewed DNA methylation and copy number aberrations in 3031 meningiomas, and studied mutation data of 858 meningiomas.…”
Section: Pathophysiology and Molecular Profile Of Cns Invasionmentioning
confidence: 99%
“…CNV data can help predict tumor behavior with the degree of chromosomal abnormalities strongly associated in recurrence [56][57][58]. This information is relatively easy to acquire at most centers and enhances its usefulness.…”
Section: Use Of Molecular Data For Recurrent Meningioma Surgerymentioning
confidence: 99%
“…While “higher risk” copy number profiles have been reported in 13–29% of grade 1 meningiomas, lesser degrees of percent genome altered are observed in some higher-grade meningiomas (Figs. 8 , 9 ) [ 56 , 58 ]. These discordances must be considered when making treatment decisions after surgery.…”
Section: Use Of Molecular Data For Recurrent Meningioma Surgerymentioning
confidence: 99%
“…The World Health Organization (WHO) classified meningiomas into three different grades, on the basis of histologic findings and presence/absence of brain invasion: grade 1, grade 2 (atypical), and grade 3 (anaplastic) [ 2 ]. This classification is widely used for prognostic stratification and guiding therapeutic management, although emerging evidence suggests that, aside from classical WHO grading, molecular profile should be taken into account for a more accurate and patient’s tailored clinical management [ 3 ].…”
Section: Introductionmentioning
confidence: 99%